Pinoy capital the Filipino nation in Daly City - Vergara, Benito M. Jr. 1970- (Asian American history and culture, 2009)
Home to 33,000 Filipino American residents, Daly City, California, located just outside of San Francisco, has been dubbed "the Pinoy Capital of the United States". This title studies the lives of Daly City residents, showing how Daly City has become a magnet for the growing Filipino American community.